MEMPERBAIKI MEDIA SECARA KOMPREHENSIF - Yustitia, Senja (Universitas Semarang, 2010)
The loss mechanism of restrictions on the media making the media business as a fertile land for hunting advantage. At first glance, this condition allows the occurrence of intense competition among media players. But, the reality is opposite. This is due to capital becomes the main strength of the business so that the media prepare a series of strategy to withstand the pressure. Media conglomerate is the answer of the conditions. Therefore, it takes maximum effort to improve the media comprehensively.